Fe1−xS@S-doped carbon core–shell heterostructured hollow spheres as highly reversible anode materials for sodium ion batteries. Issue 35 (16th August 2019) - Pan, Qichang; Zheng, Fenghua; Liu, Yanzhen; Li, Youpeng; Zhong, Wentao; Chen, Guilin; Hu, Junhua; Yang, Chenghao; Liu, Meilin
Abstract : Heterostructured Fe1− x S@S-doped carbon hollow spheres have been prepared as sodium ion battery anode material with superior rate capability and excellent long-term cycling stability. Abstract : Iron sulfide (Fe1− x S) has been considered as a promising anode material for sodium ion batteries (SIBs) because of its high theoretical capacity. However, Fe1− x S suffers from large volume change and sulfur dissolution issues during the sodiation/desodiation process, which lead to a poor cycle performance. Here, heterostructured Fe1− x S@S-doped carbon (Fe1− x S@SC) hollow spheres (HSs) have been prepared as SIB anode material. The Fe1− x S@SC HSs show a high reversible capacity of 776.2 mA h g −1 at 0.2 A g −1 and 454.3 mA h g −1 at 1.0 A g −1 after 500 cycles. The constructed Fe1− x S/SC heterojunctions play a key role in alleviating the large volume variation and stabilizing the reaction products Fe 0 and Na2 S, thus enhancing the conversion reaction kinetics of Fe 0 and Na2 S and ultimately resulting in a highly reversible conversion reaction. This work provides a possibility to solve the reversibility issue of conversion-type anode materials.